Epidemiology of speech and language impairment in a nationally representative Sample of 4- to 5-year-old Children - Harrison, L; McLeod, S; Harrison, L.J. (My University, 2009)
Purpose: To draw on multiple sources of information to determine prevalence of speech and language impairment in young Australian children. Method: Information about 4,983 children (ages 4-5 years) from Growing Up in Australia: The Longitudinal Study of Australian Children (Australian Institute of Family Studies, 2007) was obtained via parent interviews and questionnaires, teacher questionnaires, and direct assessment. Data were statistically weighted to the Australian population of 253,202 children in the target age group. Results: Parent-reported prevalence: 25.2% had concerns about how their child talked and made speech sounds (11.8% "concerned"; 13.4% "a little concerned"), and 9.5% had concerns about how their child understood language (4.4% "concerned"; 5.1% "a little concerned"). Parents who reported concerns identified "speech not clear to others" as the most frequent area of difficulty (12.0%). Teacher-reported prevalence: 22.3% of children were considered to be less competent than others in their expressive language ability (6.7% "much less competent"; 15.6% "less competent"); 16.9% were considered to be less competent than others in their receptive language ability (4.0% "much less competent"; 12.9% "less competent"). The match between parent and teacher identification was higher for expressive speech and language concern than for receptive language. Direct assessment: 13.0% of children were 1-2 SDs below the mean on the Adapted Peabody Picture Vocabulary Test-III (S. Rothman, 2003), and a further 1.7% were > 2 SDs below the mean. Parent and teacher reports were significantly correlated with scores obtained via direct assessment. Period prevalence: Parents and teachers reported that 14.5% of children had accessed speech-language pathologist (SLP) services. 2.2% indicated that they needed but could not access an SLP. Conclusion: Multiple indicators of speech and language impairment in diverse contexts confirmed the high prevalence of this condition in early childhood and a concomitant need for SLP services.
Keywords: Child Development; Child Development -- Language; Childhood and child development; Child Development; Language; Childhood and child development